Management of Patients with Guillain Barre Syndrome Accompanied by Ventilator Associated Pneumonia - Sihombing, Robert; Pison, Osmond Muftilov (Journal of Society Medicine, 2024)
Introduction: Guillain-Barré syndrome (GBS) is one of the most common autoimmune diseases affecting the peripheral nervous system in the world. This disease has manifestations of weakness, progressive muscle areflexia and can cause weakness in the respiratory muscles. This causes the patient to need mechanical ventilation assistance. Pneumonia is one of the most common complications of GBS. Ventilator-Associated Pneumonia (VAP) is one of the common nosocomial infections in 10-20% of patients on mechanical ventilators in the Intensive Care Unit (ICU). The crude mortality rate in patients who develop VAP ranges from 30-70%. In addition, VAP can significantly increase the duration of hospitalisation, as well as the cost of care. Increasing bacterial resistance in today's world makes it difficult to treat VAP with empirical antibiotic therapy. Case: A 44-year-old man came to the hospital with complaints of weakness in four limbs. The patient had previously been treated at another hospital with a diagnosis of GBS, because the patient's Erasmus GBS Respiratory Insufficiency Score (EGRIS) assessment was 5 and required further treatment in the ICU, the patient was referred to the main hospital. The complaint of being unable to move all four limbs was felt since 5 days before admission. The patient was admitted to the previous hospital for two days and received Mecobalamin, Gabapentin, and Ceftriaxone therapy. Conclusion: GBS is a post-infectious autoimmune disease that results in nerve cell destruction. Severe muscle weakness can lead to respiratory failure resulting in the need for mechanical ventilation therapy. Nosocomial pneumonia is a common complication in patients in critical condition and the leading cause of death from nosocomial infections, especially ventilator-associated pneumonia in intubated patients.